The Relationship Between Early Smoking Initiation and Drug UsePatterns Among Rehabilitation Clients : A Literature Review - Fadly Abdul Hakim; Nur Rohmah; Annisa Nurrachmawati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The age at which an individual first starts smoking plays a critical role in shaping risk behaviors associated with substance abuse. Adolescents who begin smoking at an early age are more likely to experiment with alcohol, cannabis, or synthetic drugs. Understanding the relationship between early smoking initiation and the tendency toward drug use is essential for designing effective prevention and rehabilitation strategies Objective : This study aims to review empirical evidence on the association between smoking initiation age and patterns of drug use among adolescents and rehabilitation clients in Samarinda, serving as a foundation for evidence-based prevention strategies. Research Methods/ Implementation Methods : The review analyzed 21 reputable scientific articles (Scopus Q1–Q3 and SINTA), selected based on their relevance to early smoking age, substance abuse behavior, and adolescent or rehabilitation contexts. A thematic analysis was conducted across six key areas: smoking initiation age, psychosocial factors, smoking behavior patterns, transition to drug use, media and environmental influences, and health knowledge. Results : The findings indicate that smoking before the age of 15 significantly increases the likelihood of later drug abuse. Supporting factors include peer pressure, psychological stress, and permissive environments that normalize smoking and substance use behavior Conclusion/Lesson Learned : These results highlight the urgency of implementing early preventive interventions through health education, school-based programs, and social environment supervision to reduce drug abuse rates among adolescents and support rehabilitation efforts.